2020
DOI: 10.1103/physrevb.102.035414
|View full text |Cite
|
Sign up to set email alerts
|

Transient absorption of transition metal dichalcogenide monolayers studied by a photodope-pump-probe technique

Abstract: We report three-pulse photodope-pump-probe measurements on photocarrier dynamics in semiconducting transition metal dichalcogenide monolayers of MoS 2 , WS 2 , MoSe 2 , and WSe 2 . The samples are fabricated by metal-organic chemical vapor deposition and mechanical exfoliation techniques and characterized by photoluminescence spectroscopy. In the time-resolved measurement, the samples are first photodoped by a prepulse, which injects background photocarriers of various densities. A pump pulse then injects phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Previously, we have shown that the fast decay process of the differential reflectance signal in TMD monolayers is due to the formation of excitons from pump-injected free electron−hole pairs. 32,33 The deduced exciton formation times have also been confirmed independently by another experimental technique 34 and are consistent with a theory. 35 Hence, the results suggest that the exciton formation time in MoSSe is faster than that in MoS 2 by about 30%.…”
supporting
confidence: 83%
“…Previously, we have shown that the fast decay process of the differential reflectance signal in TMD monolayers is due to the formation of excitons from pump-injected free electron−hole pairs. 32,33 The deduced exciton formation times have also been confirmed independently by another experimental technique 34 and are consistent with a theory. 35 Hence, the results suggest that the exciton formation time in MoSSe is faster than that in MoS 2 by about 30%.…”
supporting
confidence: 83%
“…Since the intercarrier scattering rate increases with their density, the decrease of the rise time with the pump fluence is reasonable. Meanwhile, excitons are also expected to form from the free electron–hole pairs on this time scale: Previous studies have revealed that in monolayer semiconductors, the exciton binding energies can reach several hundreds of millielectronvolts, , and electron–hole pairs can form excitons within 1 ps. In the nanofilm studied here, we expect similarly large exciton binding energies. Hence, the electron–hole pairs can form hot excitons in this few-picoseconds time range.…”
Section: Resultssupporting
confidence: 53%
“…The decay of the WS 2 signal is fit by a triple exponential function, Δ R / R 0 ( t ) = A 1 exp­(− t /τ 1 ) + A 2 exp­(− t /τ 2 ) + A 3 exp­(− t /τ 3 ), as shown by the cyan curve over the black squares in Figure b,c, with three decay constants (and their weights) of 0.24 ± 0.03 ps (83%), 2.4 ± 0.3 ps (9%), and 27 ± 2 ps (8%), respectively. The initial sub-picosecond fast decay has been previously assigned to the exciton formation process of the excited electron–hole pairs. The 2.4 and 27 ps processes reflect the excitonic dynamics in the monolayer WS 2 , with the latter being the exciton recombination lifetime. These results agree well with previous studies .…”
Section: Resultsmentioning
confidence: 97%